Pendampingan Branding Dan Packaging Pada UMKM Untuk Peningkatan Nilai Ekonomi - Fiandari, Yulist Rima; Shafira, Ratya; Rumijati, Aniek (SINAR SANG SURYA, 2026)
Entrepreneurial activities are a manifestation of alternative activities that can be carried out by the community in providing jobs, as well as increasing the main income. Marketing is one of the most important concepts that entrepreneurs need to do. MSME business actors need to do the right branding and package products properly to increase product competitiveness. One of the MSME actors, namely the Bumbu Pecel MSME, Bu Yuni, has not done branding and packaging on the products sold, so it is felt that it is necessary to carry out a branding and packaging assistance program for these MSMEs. The methods of activities carried out are knowledge sharing, discussion, assistance in making branding and packaging, and evaluation. The benefits obtained from service activities are that MSMEs as partners gain knowledge and attractive branding and packaging concepts that can be used to increase sales which will drive economic value for MSMEs.